2020
DOI: 10.21203/rs.3.rs-89482/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive Analysis of Genomic Mutation Signature and Tumor Mutation Burden for Prognosis of Intrahepatic Cholangiocarcinoma

Abstract: Background: The intrahepatic cholangiocarcinoma (iCCA) is highly lethal malignancy of biliary tract cancer. Analysis of somatic mutational profiling could help to reveal new prognostic markers and actionable targets for treatment. We aim to explore the impact of genomic mutation signature and tumor mutation burden (TMB) on prognosis of iCCA patients. Methods: The whole-exome sequencing and corresponding clinical data were collected from ICGC portal and cBioPortal database to detect the mutation prognostic gene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…High-Capacity cDNA revers-transcription kit (Smobio, Taiwan) was used for cDNA synthesis. Speci c primers were designed for MIAT, GAPDH using oligo primer analysis software (version 0.7.0), a speci c primer for FOXO3a was used from primer bank Harvard (Gen Bank Accession: NM_001455); and primers of miRNA29a-3p and, U6 are taken from (22). The primer sequences are shown in Table 2.…”
Section: Rt-qpcrmentioning
confidence: 99%
See 1 more Smart Citation
“…High-Capacity cDNA revers-transcription kit (Smobio, Taiwan) was used for cDNA synthesis. Speci c primers were designed for MIAT, GAPDH using oligo primer analysis software (version 0.7.0), a speci c primer for FOXO3a was used from primer bank Harvard (Gen Bank Accession: NM_001455); and primers of miRNA29a-3p and, U6 are taken from (22). The primer sequences are shown in Table 2.…”
Section: Rt-qpcrmentioning
confidence: 99%
“…Additionally, miRNA-29a-3p expression levels have been discovered to be abnormally low in a variety of human malignancies, including papillary thyroid carcinoma (PTC), hepatocellular carcinoma, and gastric cancer [22]. Previous research found that miRNA-29a-3p is involved in the progression of BC.…”
Section: Introductionmentioning
confidence: 99%